A structured and collaborative clinical teaching training programme and its influence on nursing preceptors' self-reported competencies and confidence at a national referral hospital in Uganda - Museene, Safinah Kisu (Division of Nursing and Midwifery, 2018)
Nursing practice is an outcome of good clinical teaching and learning which is facilitated by preceptors. Nursing preceptors are responsible for patient care as well as clinical teaching of nursing students. Preceptors require formal training to enable them gain appropriate pedagogical skills for conducting clinical teaching. In Uganda, there are no formal preceptorship training programs; however, clinical teaching and mentoring of nursing students is an occupational requirement. Limited information is known about the educational preparedness of nursing preceptors for their role. This study aimed to describe the preceptors' clinical teaching practices, design, implement and evaluate a structured and collaborative clinical teaching training program for improving the preceptors' pedagogical skills at a national referral hospital in Uganda. A three phase study was conducted. An initial cross-sectional survey of current preceptor clinical teaching practices and preceptors' perceived clinical teaching challenges was conducted. The survey results and relevant literature were utilised for the design of the training manual "A Structured and Collaborative Clinical Teaching Training Program" (SCCTTP). Preceptors from the national referral hospital were grouped into control and intervention groups. The intervention group completed a six-day training programme on the theories and practice of clinical teaching and the control group attended a one-day meeting where the results of the cross-sectional survey were presented. The evaluation of the training programme was conducted using a pre- and post-test design and follow-up at weeks six and twelve. The training programme demonstrated a positive influence on the intervention group's clinical teaching knowledge with a mean difference of 32.9% (P-value 0.00). Preceptors reported clinical teaching challenges which included understaffing, large numbers of students and severely ill patients. No statistical significance was found between the intervention and control groups with respect to preceptor confidence in their role as clinical facilitators. To promote quality clinical teaching practice, it is recommended that clear guidelines for preceptor training, number of students per preceptor are developed, nursing preceptors should receive formal training using the SCCTTP approach, and schools of nursing and their training hospitals collaborate and adopt a multifaceted approach to the teaching, learning and practicing of clinical skills.